New Zealand's broadcasting model as a colonial construct: A personal reflection - Royal, Haunui (Te Kaharoa, 2022)
In this paper, Haunui Royal reflects on his professional career as a filmmaker in 1980s and 1990s Aotearoa New Zealand committed to directing and producing kaupapa Māori documentaries for public television.